ByzRev 05.2023.011: Elena N. Boeck, The Bronze Horseman of Justinian in Constantinople.: The Cross-Cultural Biography of a Mediterranean Monument. Cambridge (UK): Cambridge University Press 2021. - Makris, Georgios (The Byzantine Review, 2023)
Elena N. Boeck, The Bronze Horseman of Justinian in Constantinople. The Cross-Cultural Biography of a Mediterranean Monument. Cambridge (UK): Cambridge University Press 2021. xxviii, 452 pp. – ISBN 978-1-107-19727-5 (£ 90.00; € 137.93; 122.09. Kindle £ 72.00).